Strong ground motion prediction using macro?micro analysis method. - Ichimura, T. (Earthquake engineering & structural dynamics.)
The authors propose a new analysis method, called the macro?micro analysis method (MMAM) in a companion paper. (Earthquake Engng. Struct. Dyn., this issue) for strong motion prediction with higher resolution and accuracy. The MMAM takes advantage of the bounding medium theory to obtain optimistic and pessimistic estimates of the expected strong motion and the singular perturbation expansion that leads to an efficient multi-scale analysis. The results of the numerical simulation with the MMAM are given as the sum of waves of low resolution covering the whole city and waves of high resolution for each part of the city. While the huge computation amount is reduced by the MMAM, the computation amount is huge still. For resolving this problem, this paper applies the finite element method with voxel element to numerical simulation tools after some numerical verification. To reproduce complicated material properties of surface soft deposits, fundamental hysteresis attenuation is implemented in the three-dimensional simulation code. The proposed method is verified by carrying out the strong motion prediction with MMAM and comparing with measured data. In addition, the effect of three-dimensional soil?structure and frequency component on the maximum velocity distribution, which is simulated by proposed method with high spatial resolution, is discussed.